Religion in the Egyptian novel - Phillips, Christina (Edinburgh studies in modern Arabic literature., 2019)
This is an in-depth, original survey of religion in the modern Arabic novel. Tracing the relationship from the genesis of the form in the early twentieth century to present, Phillips provides a thematic exploration of the push and pull between religion and secularism as it played out on the pages of the Egyptian novel.